2024
DOI: 10.5713/ab.23.0246
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors influencing milk and fat yields in tropically adapted dairy cattle: insights from quantitative trait loci analysis and gene associations

Thawee Laodim,
Skorn Koonawootrittriron,
Mauricio A. Elzo
et al.

Abstract: Objective: The objective of this study was to identify genes associated with 305-day milk yield (MY) and fat yield (FY) that also influence the adaptability of the Thai multibreed dairy cattle population to tropical conditions.Methods: A total of 75,776 imputed and actual single nucleotide polymorphisms (SNPs) from 2,661 animals were used to identify genomic regions associated with MY and FY using the single-step genomic best linear unbiased predictions. Fixed effects included herd-yearseason, breed regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Recent research has indicated that DGKB has been identified through GWAS as potentially related to bone and muscle development in Chinese gamecocks populations ( Ren et al, 2023 ). Regarding CTNNA2 , it has been reported to be associated with milk fat production in cows ( Laodiim et al, 2023 ) and is also implicated in lipid metabolism ( Schooling, 2016 ). CTNNA2 emerges as the highest hub gene in the interaction network and makes a significant contribution to muscle development ( Malik et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has indicated that DGKB has been identified through GWAS as potentially related to bone and muscle development in Chinese gamecocks populations ( Ren et al, 2023 ). Regarding CTNNA2 , it has been reported to be associated with milk fat production in cows ( Laodiim et al, 2023 ) and is also implicated in lipid metabolism ( Schooling, 2016 ). CTNNA2 emerges as the highest hub gene in the interaction network and makes a significant contribution to muscle development ( Malik et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%